Mechanisms of subglacial cavity filling in Glacier de Tête Rousse, French Alps - Vincent, C.; Thibert, Emmanuel; Gagliardini, O.; Legchenko, A.; Gilbert, A.; Garambois, S.; Condom, T.; Baltassat, Jean-Michel; Girard, Jean-François (Journal of Glaciology, 2015)
[Departement_IRSTEA]Eaux [TR1_IRSTEA]RIVAGE International audience The deadliest outburst flood from an englacial cavity occurred on Glacier de Tete Rousse in the Mont Blanc area, French Alps, in 1892. A subglacial reservoir was discovered in the same glacier in 2010 and drained artificially in 2010, 2011 and 2012 to protect the 3000 inhabitants downstream. The mechanism leading to the spontaneous refilling of the cavity following these pumping operations has been analyzed. For this purpose, the subglacial water volume changes between 2010 and 2013 were reconstructed. The size of the cavity following the pumping was found to have decreased from 53 500 m(3) in 2010 to 12 750 m(3) in 2013. Creep and the partial collapse of the cavity roof explain a large part of the volume loss. Analysis of cavity filling showed a strong relationship between measured surface melting and the filling rate, with a time delay of 4-6 hours. A permanent input of 15 m(3) d(-1), not depending on surface melt, was also found. The meltwater and rain from the surface is conveyed to bedrock through crevasses and probably through a permeable layer of rock debris at the glacier bed. The drainage pathway permeability was estimated at 0.054 m s(-1) from water discharge measurements and dye-tracing experiments.